Preliminary study of CT features of intermediate- and high-grade alimentary lymphoma and adenocarcinoma in cats. Issue 10 (October 2022) - Tanaka, Toshiyuki; Noguchi, Shunsuke; Wada, Yusuke; Nishida, Hidetaka; Akiyoshi, Hideo
Case series summary: The ultrasonographic findings of many feline intestinal tumours are similar. This study evaluated the CT features of intermediate- and high-grade alimentary lymphoma and adenocarcinoma in cats. CT was performed on six cats with adenocarcinoma and 14 cats with lymphoma. Comparisons between tumour types were conducted, focusing on CT features, including obstruction (present or absent), growth patterns of lesions (symmetry or asymmetry), layering enhancement (present or absent), location of the lesion, number of lesions (solitary or multiple), lymphadenopathy (present or absent), location of lymphadenopathy, pulmonary metastasis (present or absent) and maximum thickness (mm) of the lesion. The cats with adenocarcinoma (n = 5/6 [83%]) experienced intestinal obstruction significantly more often than cats with lymphoma (n = 0/14 [0%]; P  = 0.0004). Layering enhancement was observed significantly more often in cats with adenocarcinoma (n = 6/6 [100%]) than in cats with lymphoma (n = 1/14 [7%]; P  = 0.0002). Lymphadenopathy was detected significantly more often in cats with lymphoma (n = 14/14 [100%]) than in cats with adenocarcinoma (n = 2/6 [33%]) ( P  = 0.003). In cats with lymphoma, the intestine (12.1 ± 3.9 mm) was significantly thicker than that in cats with adenocarcinoma (6.4 ± 2.3 mm; P  = 0.005). Relevance and novel information: To the best of our knowledge, no reports have described the characteristics of feline intestinal tumours using CT. Layering enhancement was observed in cats with intestinal adenocarcinomas. No layering enhancement was observed in alimentary lymphoma in cats, but enlarged regional nodes were noted. Lesions with lymphoma were thicker than those with adenocarcinoma. These findings may help differentiate between adenocarcinomas and lymphomas.